1996
DOI: 10.1143/jjap.35.6458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Vibration on Patterning Characteristics in Synchrotron Radiation Lithography

Abstract: In order to improve pattern precision and overlay accuracy in synchrotron radiation (SR) X-ray lithography, it is required that a stepper be very stable mechanically and have a high positioning accuracy with regard to both the mask-to-wafer gap and the stage. It is important to clarify the effect of mechanical vibrations on patterning characteristics. We investigated the effect of mechanical vibrations on line-and-space patterns with dimensions of less than 0.2 µ m by carrying out exposure experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For instance, it is reported that the amplitude of floor vibrations at KEK's accelerator test facility ATF2 project is approximately 50 mm, which is even larger than the vertical beam spot size expected at ATF2 (Masuzawa et al, 2006). In another report related to synchrotron radiation lithography, the quality of microstructures fabricated by the lithography beamline is greatly affected when the amplitude of the vibration is larger than a quarter of the minimum feature size (Fukuda et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is reported that the amplitude of floor vibrations at KEK's accelerator test facility ATF2 project is approximately 50 mm, which is even larger than the vertical beam spot size expected at ATF2 (Masuzawa et al, 2006). In another report related to synchrotron radiation lithography, the quality of microstructures fabricated by the lithography beamline is greatly affected when the amplitude of the vibration is larger than a quarter of the minimum feature size (Fukuda et al, 1996).…”
Section: Introductionmentioning
confidence: 99%